(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic determined new forms of organization in all sectors of society, including the educational sector that needed to reinvent itself in terms of methodological procedures, especially regarding the insertion of technological resources for the development of classes. In this context, the STEAM approach based on interdisciplinary projects using technology, envisions a new way of organizing the curriculum that aims to integrate curriculum components, student protagonist and education aimed at solving real problems encountered in the community. Thus, the objective of this article was to apply the STEAM Approach (Science, Technology, Engineering, Arts and Mathematics) through an interdisciplinary project on the psychological and social consequences of COVID-19 in the 8th Year of Elementary School, in a public school, aiming to the development of skills and abilities present in the official documents of Brazil and the state of Mato Grosso, BNCC and DRC-MT. For the development of the research, the applied qualitative approach was used, as well as the bibliographic research with an action research format, regarding the procedures. he subjects of this investigation were teachers of the curricular components, Natural Sciences, Art and Mathematics of a public school located in a city in the western region of Mato Grosso and students of the 8th year of the same school. Data collection was carried out through participant observation during the construction and execution of the actions of the project entitled: The psychological and social consequences of the COVID-19 pandemic. The results showed that students develop skills and abilities when challenged, especially when carrying out investigation and prototype building activities as mentioned in the STEAM Approach.